Trivial isolated bilateral clavicle fracture : a case report - Mohamad Ridhwan, Mohd Muhaimin; Ong, Lik Han; Phang, Z. H (MALAYSIAN ORTHOPAEDIC ASSOCIATION, 2023)
INTRODUCTION: Bilateral clavicle fracture is a rare occurrence and associated with high energy trauma.1 We would like to present a case report of a patient sustained bilateral clavicle fracture after a low energy trauma.